Discourse on Creole Identity: from Ambivalence to Madness Post-Colonial Reading on Rhys’ Wide Sargasso Sea - Subhan, Asep; Turuk, Didimus E. (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2019)
The portrayal of creole identity is presented in several literary works, one of them is in the portrayal of Antoinette Cosway in Jean Rhys’ Wide Sargasso Sea. Antoinette Cosway firstly is the minor character in Charlotte Brontë’s Jane Eyre. The research traces the link between Antoinette Cosway’s creole identity with her madness. According to Bhabha’s ambivalence theory, creole identity possibly creates a new identity as the result of interrelation between colonizer and colonized. Based on the research, Antoinette Cosway failed to create a new identity and became a madwoman instead. The cause is the complex situation faced by her and the lack of supporting aspects for constructing a new identity. Keywords: creole identity, ambivalence, Antoinette Cosway, Homi Bhabha